The Spread of the Cult of Josaphat Kuntsevych through the Cyrillic Texts of the Basilian Printing Houses in the Polish-Lithuanian Commonwealth - Bondar, Nataliia; Zabolotna, Nataliia (Lietuvos istorijos studijos, 2025)
Over time, publications produced in Vilnius, Lviv, Supraśl, Univ, and Pochaiv came to reflect the cult of Josaphat Kuntsevych, and were designed to meet the needs of the Uniate Church. A service dedicated to him was included in the Liturgikon and Menaion, and a book called Возслідування празникам (Celebration of the Feasts). In Lviv, the service was published as a separate edition, with the text of the service changing over time. In addition to the service, the Life of St. Josaphat, along with his image, were also published (Pochaiv Menaion). Other pieces, dedicated to Josaphat Kuntsevych, are the songs in Pochaiv Bohohlasnyk (Hymn Book), and the sermons by Yulian Dobrylovsky in the ‘Parochial Lessons’. The largest and most diverse contribution to honouring Josaphat Kuntsevych in terms of quantity and genre was created by the Pochaiv printing house. Pochaiv publications in Latin script also contributed to the spread of his cult. The marginalia in the books, which mention the blessed man, testify to the indifferent attitude which readers, including Orthodox believers, had towards this religious personality.